Bioresorbable stents: Current and upcoming bioresorbable technologies. (1st February 2017) - Ang, Hui Ying; Bulluck, Heerajnarain; Wong, Philip; Venkatraman, Subbu S.; Huang, Yingying; Foin, Nicolas
Abstract: Bioresorbable scaffolds (BRS) represent a novel horizon in interventional cardiology for the treatment of coronary artery disease. The technology was introduced to overcome limitations of current metallic drug-eluting stents such as late in-stent restenosis and permanently caging the vessel. The concept of the BRS is to provide temporal support to the vessel during healing before being degraded and resorbed by the body, promoting restoration of the vessel vasomotion. Currently, there are several BRS that are under development or already commercially available. Although several reviews have elegantly covered progress of current clinical programs and newer scaffold technologies, little is available currently to describe the mechanistic differences between biomaterials used in current and newer bioresorbable technologies. This aim of this review is to discuss the status of the different BRS technologies and materials currently under investigation, explore the newer strategies being adopted to improve material mechanical properties and optimize BRS degradation and summarize the performance of BRS in the clinical setting so far. Highlights: A review of current methods to develop polymeric bioresorbable scaffolds (BRS) The effects of materials and processing approaches on mechanical properties Provided a summary of some of the current BRS technologies and the materials Discussed methods to improve radiopacity of the polymeric BRS A summary of the use of absorb BVS in clinical setting